Capital account convertibility in India - Bengal Economic Association (Kolkata, India). Annual Conference 2007 : Kolkata, India); Chatterjee, Biswajit; Karmakar, Asim K., 1956- (New Delhi : Deep & Deep Publications, 2011)
Papers presented at the twenty-seventh annual Conference of the Bengal Economic Association, held at Calcutta in 2007.
"Published on behalf of the Bengal Economic Association."
Includes bibliographical references and index.
Keywords: Capital movements -- India -- Congresses; India -- Economic policy -- 1991- -- Congresses